What goes around comes around: the circulation of proverbs in contemporary life - Lau, Kimberly J., editor; Tokofsky, Peter, editor; Winick, Stephen D., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2004)
In this collection of essays prominent folklorists look at varied modern uses and contexts of proverbs and proverbial speech, some traditional and conventional, others new and unexpected. After the editors' introduction discussing the history and status of attempts to define proverbs, describing their contemporary circulation, and acknowledging the especially important work of paremiologist Wolfgang Meider, the contributions examine the continuing pervasiveness and idiomatic relevance of proverbs in modern culture.
What goes around comes around: the circulation of proverbs in contemporary life / Kimberly J. Lau, Peter Tokofsky, and Stephen D. Winick -- "In aqua scribere": the evolution of a current proverb / Charles Clay Doyle -- "From one act of charity, the world is saved": creative selection of proverbs in Sephardic narrative / Isaac Jack Lévy and Rosemary Lévy Zumwalt -- Baseball as (pan)America: a sampling of baseball-related metaphors in Spanish / Shirley L. Arora -- "You can't kill shit": occupational proverb and metaphorical system among young medical professionals / Stephen D. Winick -- "Cheaters never prosper" and other lies adults tell kids: proverbs and the culture wars over character / Jay Mechling -- The proverb and fetishism in American advertisements / Anand Prahlad -- "The early bird is worth two in the bush": Captain Jack Aubrey's fractured proverbs / Jan Harold Brunvand -- As the crow flies: a straightforward study of lineal worldview in American folk speech / Alan Dundes.
Keywords: Mieder, Wolfgang; Proverbs -- History and criticism